Association between physical activity and quality of life in the elderly: a systematic review, 2000-2012 - Vagetti,Gislaine C. (2014)
Objective: To review information regarding the association of physical activity (PA) with quality of life (QoL) in the elderly and to identify the study designs and measurement instruments most commonly used in its assessment, in the period 2000-2012. Methods: Relevant articles were identified by a search of four electronic databases and cross-reference lists and by contact with the authors of the included manuscripts. Original studies on the association between PA and QoL in individuals aged 60 years or older were examined. The quality of studies as well as the direction and the consistency of the association between PA and QoL were evaluated. Results: A total of 10,019 articles were identified as potentially relevant, but only 42 (0.42%) met the inclusion criteria and were retrieved and examined. Most studies demonstrated a positive association between PA and QoL in the elderly. PA had a consistent association with the following QoL domains: functional capacity; general QoL; autonomy; past, present and future activities; death and dying; intimacy; mental health; vitality; and psychological. Conclusion: PA was positively and consistently associated with some QoL domains among older individuals, supporting the notion that promoting PA in the elderly may have an impact beyond physical health. However, the associations between PA and other QoL domains were moderate to inconsistent and require further investigation.